1987
DOI: 10.2170/jjphysiol.37.207
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the mode of acute cold-induced hypothermia between rat and hamster.

Abstract: The present work was undertaken to elucidate the underlying causative factors limiting survival in hypothermic rats (non-hibernator) and hamsters (hibernator). A variety of physiological and biochemical parameters were measured for 28 male Wistar rats (205-286 g) and 26 male golden hamsters (85-118 g) before and during induction of hypothermia to colonic temperature (Tco) of 18°C. With progressive decreases in Tco, parallel falls in Vo2, Vco2, and heart rate were observed. In rats, plasma pH (pH) in arterial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
2
2
Order By: Relevance
“…The constant pHa (⌬pHa/⌬Tb ϳ0.002 U/°C) of the rats in this study differs from previous studies using unanesthetized rats during forced hypothermia, where ⌬pHa/⌬Tb has been shown to range from Ϫ0.0015 to Ϫ0.009 U/°C (2,3,63,66). Discrepancies may be related to methodologies used such as restraint with potential stress-related effects on blood gases and acid-base balance (63) or shaving, which can alter behavioral adaptations to cold stress (2, 3), such as gross movement, piloerection, and postural adjustments that reduce surface area. In addition, restraint can further confound findings by causing increased V E (15), increased V O 2 with no corresponding increase in V E (55), and increased plasma corticosterone levels, heart rate, and arterial blood pressure (33).…”
Section: E V O 2 and Pha Regulation During Hypothermia: Comparatcontrasting
confidence: 81%
See 1 more Smart Citation
“…The constant pHa (⌬pHa/⌬Tb ϳ0.002 U/°C) of the rats in this study differs from previous studies using unanesthetized rats during forced hypothermia, where ⌬pHa/⌬Tb has been shown to range from Ϫ0.0015 to Ϫ0.009 U/°C (2,3,63,66). Discrepancies may be related to methodologies used such as restraint with potential stress-related effects on blood gases and acid-base balance (63) or shaving, which can alter behavioral adaptations to cold stress (2, 3), such as gross movement, piloerection, and postural adjustments that reduce surface area. In addition, restraint can further confound findings by causing increased V E (15), increased V O 2 with no corresponding increase in V E (55), and increased plasma corticosterone levels, heart rate, and arterial blood pressure (33).…”
Section: E V O 2 and Pha Regulation During Hypothermia: Comparatcontrasting
confidence: 81%
“…Thus neither ectothermic nor endothermic joeys conform to the values predicted by the ␣-stat hypothesis (50) and often observed in reptiles (e.g., 10,16,20). The constant pHa (⌬pHa/⌬Tb ϳ0.002 U/°C) of the rats in this study differs from previous studies using unanesthetized rats during forced hypothermia, where ⌬pHa/⌬Tb has been shown to range from Ϫ0.0015 to Ϫ0.009 U/°C (2,3,63,66). Discrepancies may be related to methodologies used such as restraint with potential stress-related effects on blood gases and acid-base balance (63) or shaving, which can alter behavioral adaptations to cold stress (2, 3), such as gross movement, piloerection, and postural adjustments that reduce surface area.…”
Section: E V O 2 and Pha Regulation During Hypothermia: Comparatcontrasting
confidence: 80%
“…Despite evidence for global forebrain depression, torpid hibernators maintain a robust, neuronally regulated cardiorespiratory output (37,25,41), suggesting that respiratoryand cardiovascular-related neurons in the brain stem remain active. The mechanisms that selectively depress the forebrain during hibernation are not well understood and may contribute to hibernators' unique ability to survive ischemia, hypovolemia, and hypothermia (5,12,31,34,66).While euthanizing aroused hibernators for an unrelated study, we noted that pentobarbital sodium, an allosteric modulator of gamma aminobutyric acid type A (GABA A ) receptors, when used at doses sufficient for euthanasia, rapidly immobilized animals yet had no observable effect on respiratory rhythm. Subsequently, we began to investigate the role of GABA and GABAergic synaptic transmission in respiratory control during hibernation.…”
mentioning
confidence: 99%
“…Despite evidence for global forebrain depression, torpid hibernators maintain a robust, neuronally regulated cardiorespiratory output (37,25,41), suggesting that respiratoryand cardiovascular-related neurons in the brain stem remain active. The mechanisms that selectively depress the forebrain during hibernation are not well understood and may contribute to hibernators' unique ability to survive ischemia, hypovolemia, and hypothermia (5,12,31,34,66).…”
mentioning
confidence: 99%